2017
DOI: 10.4274/balkanmedj.2017.0350
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Fibrous Tumors of Chest: Another Look with the Oncologic Perspective

Abstract: Solitary fibrous tumors are mesenchymal lesions that arise at a variety of sites, most commonly the pleura. Most patients are asymptomatic at diagnosis, with lesions being detected incidentally. Nevertheless, some patients present due to symptoms from local tumor compression (eg. of the airways and pulmonary parenchyma). Furthermore, radiological methods are not always conclusive in making a diagnosis, and thus, pathological analysis is often required. In the past three decades, immunohistochemical techniques h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 71 publications
3
21
0
6
Order By: Relevance
“…SFT were originally described in the pleura by Klemperer and Rabin in 1931,4 consistent with most series finding a thoracic origin in up to 70% of the cases (80% pleural, 10% mediastinal and 10% intrapulmonary) 5. Today, SFT are known to arise from many extrathoracic tissues including but not limited to head and neck, retroperitoneum, peritoneum, abdomen, meninges, orbit, upper respiratory tract, salivary glands, thyroid, liver, adrenal gland, kidney, spermatic cord, urinary bladder, prostate, uterine cervix, spinal cord and periosteum 4…”
Section: Discussionsupporting
confidence: 66%
“…SFT were originally described in the pleura by Klemperer and Rabin in 1931,4 consistent with most series finding a thoracic origin in up to 70% of the cases (80% pleural, 10% mediastinal and 10% intrapulmonary) 5. Today, SFT are known to arise from many extrathoracic tissues including but not limited to head and neck, retroperitoneum, peritoneum, abdomen, meninges, orbit, upper respiratory tract, salivary glands, thyroid, liver, adrenal gland, kidney, spermatic cord, urinary bladder, prostate, uterine cervix, spinal cord and periosteum 4…”
Section: Discussionsupporting
confidence: 66%
“…13,14 Most SFTs are benign, but MSFT, which accounts for 10-20% of all SFTs, has a higher recurrence and metastatic rate, and relatively poor survival. 5,6 Tumour sizes larger than 10 cm appear to be malignant, and the tumour size in the present case was larger than 10 cm, both before and after the conversion chemotherapy, indicating a malignant tumour. Although 18F-FDG PET/CT may be helpful in diagnosing MSFT, its diagnostic utility remains debatable due to its imperfect sensitivity.…”
Section: Discussionmentioning
confidence: 45%
“…We have previously published clinical outcomes after radiosurgery or whole brain radiation for brain metastasis of various histologic types [19,20]. Radiation therapy is especially utilized in cases with malignant SFT, narrow margins, tumor size greater than 10 cm, and fast-growing tumors [2]. For example, in an analysis of 102 SFT cases, Krengli et al reported that local control was higher in patients who were treated with surgery plus postoperative radiation therapy when compared to surgery alone [21].…”
Section: Discussionmentioning
confidence: 99%
“…SFTs are most commonly benign, but 10-20% of cases have been reported to be malignant. SFTs usually occur in middle-aged patients and equally in men and women [2]. e most common sites for metastasis are the lungs (61%), pleura (49%), liver (41%), bones (41%), and peritoneum (41%) [3].…”
Section: Introductionmentioning
confidence: 99%